2019
DOI: 10.1002/1873-3468.13326
|View full text |Cite
|
Sign up to set email alerts
|

SWAP70 undergoes dynamic conformational regulation at the leading edge of migrating cells

Abstract: Rearrangements of the actin cytoskeleton are regulated in part by dynamic localised activation and inactivation of Rho family small GTPases. SWAP70 binds to and activates the small GTPase RAC1 as well as binding to filamentous actin and PIP3. We have developed an encoded biosensor, which uses Forster resonance energy transfer to reveal conformational changes in SWAP70 in live cells. SWAP70 adopts a distinct conformation at the plasma membrane, which in migrating glioma cells is enriched at the leading edge but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…SLC2A10 regulated fibroblasts in arterial tortuosity syndrome by encoding glucose transporter 10 ( 41 ). The PI3K-dependent recruitment of SWAP70 to the plasma membrane has been observed in growth factor-stimulated fibroblasts ( 42 ). EMP3 plays an important role in the regulation of membrane receptors associated with IDH-Wild type glioblastoma ( 43 ).…”
Section: Discussionmentioning
confidence: 98%
“…SLC2A10 regulated fibroblasts in arterial tortuosity syndrome by encoding glucose transporter 10 ( 41 ). The PI3K-dependent recruitment of SWAP70 to the plasma membrane has been observed in growth factor-stimulated fibroblasts ( 42 ). EMP3 plays an important role in the regulation of membrane receptors associated with IDH-Wild type glioblastoma ( 43 ).…”
Section: Discussionmentioning
confidence: 98%
“…Intravital measurements of FRET are achieved by either ratiometric measurements of donor and acceptor signals, by measuring the sensitized emission of the acceptor, or by measuring the donor's fluorescence lifetime (FLIM) (Piston and Kremers 2007;Jalink 2013;Conway et al 2014;Martin et al 2018). Cell motility can be studied using for example FRET-reporters for RhoA (Nobis et al 2017), Rac (Johnsson et al 2014;Yukinaga et al 2014), Src (Nobis et al 2013a;Vennin et al 2017), SWAP70 (Kriplani et al 2019), Arf6 (Hall et al 2008), or FAK (Seong et al 2013) activity.…”
Section: Ivm Of Fluorescent Properties To Reveal Molecular Eventsmentioning
confidence: 99%
“…SWAP-70 has been described as a unique F-actin regulatory protein, which binds and bundles F-actin (25), and has several non-redundant functions in various hematopoietic cells such as polarization (26), endocytosis (27), integrin-mediated adhesion (28,29), migration (30), and homing (26). In many of these cell types, it was observed that SWAP-70 localizes to sites of active F-actin rearrangement (31)(32)(33)(34)(35)(36). Swap-70 -/mice exhibit an osteopetrotic phenotype, characterized by increased bone mineral density caused by decreased resorptive activity of osteoclasts defective in F-actin ring formation (31,35).…”
Section: Introductionmentioning
confidence: 99%